The efficacy of contemporary law of the sea in suppressing piracy and maritime terrorism - Ahmed, Md. Hassan (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2014)
The safety of maritime navigation has always been in the midst of threat of piracy and maritime terrorism due to the lack of efficient legal regime and cooperative arrangements among States. This compelling situation forces the international community to create regulatory frameworks which effectively suppresses such maritime crimes. The researcher, therefore, aims to carry out the current study in order to identify, examine, analyse deficiencies and propose viable solutions to those shortcomings in the contemporary international law of the sea conventions, regional agreements and regional arrangements pertaining to the suppression of piracy and maritime terrorism, namely: the High Sea convention, the UNCLOS, the SUA Convention, the 2005 Protocol, the ReCAAP, the Djibouti Code of Conduct and the MSP in the Malacca Straits. The research is primarily doctrinal and the researcher employs multidimensional methods of legal research, predominantly by qualitative methods. The researcher applies analytical approach in examining the efficacy of aforesaid contemporary international law of the sea. The comparative approach is also used to appraise various definitions of piracy, armed robbery against ships and unlawful acts against the safety of maritime navigation; and provisions relating to jurisdiction, extradition, prosecution, right of visit, arrest of ships as well as offenders under these legal regimes. After careful analysis of the contemporary law of the sea, it is found that the regulatory framework for the effective suppression of such maritime crimes should be implemented at both international and regional levels. At the international level, the UNCLOS and the SUA Convention can be maintained as they are despite some shortcomings. Nevertheless, the 2005 Protocol should be restructured with regard to the PSI issue, the right of visit as well as boarding procedures for the purpose of meeting the expectation of the international community and to be an efficient legal regime which complements to the SUA convention. In addition, although the suppression of piracy and maritime terrorism is a global menace, States are reluctant, to some extent, in implementing their obligations for combating such maritime crimes under the international law of the sea conventions. They are more participative in carrying out their obligations and measures offered under regional agreements. Hence, the researcher humbly suggests that it would be more effective to supplement aforesaid international conventions with regional agreements which can provide more pragmatic solutions to address issues relating to definitions of maritime crimes; guidelines for the exercise of jurisdiction, prosecution as well as extradition; and other cooperative measures among neighbouring States such as information sharing, patrolling and capacity building. The significance of the current research is that the study mainly focuses in evaluating and examining the efficacy of the contemporary law of the sea in suppressing piracy and maritime terrorism at both international as well as regional levels. It is humbly hoped that this research would greatly contribute not only in ensuring the safety of maritime navigation all around the world but also in maintaining international peace and security.